"The Bad Landlord": Origins and Significance in Contemporary Housing Policy and Practice. Issue 4 (8th August 2021) - Roberts, Simon; Satsangi, Madhu
ABSTRACT: The "bad landlord" is an important stereotype in political debate. This paper applies Foucault's analysis of historical change in the relation between economics and government, to examine the changing use of this stereotype the UK since the nineteenth century. We trace how this development reflects changes in the nature of government over this period. An analysis of debates on landlordism in the post-devolution Scottish Parliament demonstrates how the stereotype is used in the context of devolved government.